Yield and water productivity of Buffel and Rhodes grasses under different irrigation water regimes using the sprinkler line‐source system. (April 2016) - Mazahrih, Naem; Al‐Wahaibi, Hamdan; Al‐Farsi, Safa; Ouled Belgacem, Azaiez
Abstract: The indigenous forage species such as Buffel grass ( Cenchrus ciliaris) are capable of surviving with less water than most introduced species such as Rhodes grass ( Chloris gayana ) and alfalfa. However, the productivity of Buffel grass as a function of the amount of water applied is unknown. A case study was conducted in Oman to evaluate the response of Buffel and Rhodes grasses to different irrigation levels using line‐source sprinkler irrigation system. Four irrigation treatments (40, 65, 100 and 125%) based on reference evapotranspiration (ETo ) with two grass species (Buffel and Rhodes grasses) were investigated as sub‐main treatments in strip plot design with four replications. The average total amount of applied water during the study period were 15 126, 24 580, 37 815 and 47 269 m 3  ha −1, for the four irrigation treatments, respectively. The results of 12 cuts during 514 days indicated that Buffel grass has significantly higher dry weight production (DW) and water productivity than Rhodes grass at all irrigation levels. Irrigation by 65% of ETo for Buffel grass has the highest water productivity value reached to 0.95 kg m −3 and 42% of applied water can be saved to produce the same amount of DW of Rhodes grass. Soil salinity increased in the soil profile for 40, 65 and 100% ETo irrigation levels during the summer season and the soil salinity values were higher at Rhodes than Buffel grasses location for these irrigation levels.